Resistance of the micromycetes isolated from the chernozem usual and technozems to the joint influence of cadmium, nickel, copper, zinc, and lead - Gryshko, V.M.; Korinovskaya, O.M.; Krumova, E.; Angelova, M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The resistance of micromycetes to the joint impact of cadmium, zinc, nickel, copper, and lead compounds is studied. The most sensitive to the minimum content of heavy metals (Cu2+ and Cd2+ — 2.25; Ni2+ — 3.0; Pb2+ — 15.0; Zn2+ — 17.5 mg/l) on the Capek medium were Absidia butleri, Mortierella vnacea, Cunninghamella echinulata, Curvularia tuberculata, and Fusarium solani. For Trichoderma longibrachiatum, Alternaria alternata, Penicillium sp4, and Mucor globosus, a weak growth even at the maximum concentration (Cu2+ and Cd2+ — 150; Ni2+ — 200; Pb2+ — 1000; Zn2+ — 1150 mg/l) was noticed. It is shown that Botrytis cinerea and Mortierella jenkini most actively accumulated cadmium, B. cinerea, Aspergillus wentii, M. jenkini, T. longibrachiatum — nickel, Aspergillus niger, Fusarium oxysporum, and Penicillium vinaceum — copper, M. jenkini — zinc. The majority of micromycetes had the smallest rates of zinc accumulation in comparison with other metals.